2004
DOI: 10.1017/s0022029903006381
|View full text |Cite
|
Sign up to set email alerts
|

Fate of ivermectin residues in ewes' milk and derived products

Abstract: The fate of ivermectin (IVM) residues was studied throughout the processing of daily bulk milk from 30 ewes (taken up to 33 d following subcutaneous administration of 0 . 2 mg IVM/kg b.w.) in the following milk products: yoghurt made from raw and pasteurized milk; cheese after pressing ; 30-and 60-day ripened cheese; and whey, secondary whey and whey proteins obtained after cheese-making (albumin cheese). The concentration of the H 2 B 1a component of IVM was analysed in these dairy products using an HPLC meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 7 publications
2
31
2
Order By: Relevance
“…Residues of ivermectin in biological fluids are stable for up to one year after freezing (Cerkvenik et al, 2004) and the analysis of ivermectin in the fluids and tissues was performed within 3 months of collection. Ivermectin was analyzed in plasma and tissue by high-performance liquid chromatography (HPLC) with automated solid phase extraction and fluorescence detection according to a previously described method (Lifschitz et al, 2000).…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…Residues of ivermectin in biological fluids are stable for up to one year after freezing (Cerkvenik et al, 2004) and the analysis of ivermectin in the fluids and tissues was performed within 3 months of collection. Ivermectin was analyzed in plasma and tissue by high-performance liquid chromatography (HPLC) with automated solid phase extraction and fluorescence detection according to a previously described method (Lifschitz et al, 2000).…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…Anastassio et al found that residue levels of ivermectin (sc 200 g/kg bw), reached a maximum concentration of 29 g/kg in buffalo milk at 2.5 days post-treatment and residues were detectable at 20 days post-treatment at a level of 0.6 g/kg [69]. Cerkvenik-Flajs et al investigated the fate of ivermectin residues in ewes' milk and dairy products (raw bulk milk, yoghurt from raw and pasteurised milk, cheese and whey) from ewes undergoing a residue depletion trial [70]. Highest levels of ivermectin residues were determined at 2 days withdrawal in raw milk (22 g/kg), yoghurt (23 g/kg), cheese (96 g/kg) and at 1 day withdrawal in albumin cheese (31 g/kg).…”
Section: Ivermectinmentioning
confidence: 97%
“…However, gradient elution has been used by a number of researchers [54,70,119,126,131,138,143,169]. Gradient elution may be used to separate the residues or to remove late eluting interferences from the column that may interfere with subsequent determination [131,132,138,143,169].…”
Section: 1 Liquid Chromatography Separationsmentioning
confidence: 99%
“…Toutain et al (1988) indicated that IVM residues were still excreted in cow's milk at 29 days post subcutaneous application. Furthermore, IVM was detected in milk products made from milk of treated sheep (Cerkvenik et al 2004a;Cerkvenik et al 2004b). IVM is substantially excreted into the milk because of its lipophilicity; for this reason its use during the lactation period must be prohibited.…”
Section: Introductionmentioning
confidence: 99%
“…IVM is substantially excreted into the milk because of its lipophilicity; for this reason its use during the lactation period must be prohibited. Treatment with IVM is banned at least 21-33 days before lambing (Cerkvenik et al 2004b), but for some, even accidental reasons (Davis 1991), its use with lactating animals cannot always be avoided. The instructions for its use clearly state that the withdrawal time was not determined for milk.…”
Section: Introductionmentioning
confidence: 99%